Time evolution of piglet cerebral blood volume after resuscitation from hypoxic-ischemic insult - Manabu Machida; Tsutomu Mitsuie; Yasuhiro Nakao; Yinmon Htun; Aya Morimoto; Uiko Hanaoka; Yukihiko Konishi; Kosuke Koyano; Shinji Nakamura; Takashi Kusaka (Scientific Reports)
Abstract Neonatal hypoxic-ischemic encephalopathy (HIE) is a significant cause of neonatal mortality and developmental disabilities. It has been revealed that the temporal behavior of the cerebral blood volume (CBV) carries information on the degree of hypoxia-ischemia. CBV can be estimated by means of near-infrared spectroscopy. The change of CBV after the insult is related to the change of CBV during the insult. In this paper, we consider a mathematical model which governs the time evolution of CBV after the insult. We show that the temporal behavior of CBV can be predicted with the Kalman filter which is based on the mathematical model. Finding a governing equation opens up possibilities for a more quantitative diagnosis of HIE.